Прогнозування зміни вихідних характеристик планетарного гідромотора в умовах експлуатації - Панченко, Анатолій Іванович; Волошина, Анжела Анатоліївна; Ковязін, Олексій Сергійович; Панченко, Ігор Анатолійович; Волошин, Анатолій Анатолійович; Panchenko, Anatolii; Voloshina, Angela; Koviazin, Oleksii; Panchenko, Ihor; Voloshin, Anatolii (Запоріжжя : Видавничий дім «Гельветика», 2026)
UA: У роботі досліджено зміну вихідних характеристик планетарного гідромотора в процесі експлуатації з урахуванням його технічного стану. Встановлено, що ключовим фактором деградації параметрів є збільшення діаметрального зазору між роторами, яке впливає на частоту обертання, витрату робочої рідини та енергетичні показники. На основі повного факторного експерименту обґрунтовано вибір визначальних факторів (навантаження, витрата, зазор) та отримано математичні моделі у вигляді рівнянь регресії, що адекватно описують робочі процеси з довірчою ймовірністю 0,95. Встановлено, що коефіцієнт корисної дії є малочутливим до зміни технічного стану, тоді як частота обертання є найбільш інформативним діагностичним параметром. Отримані залежності дозволяють визначати технічний стан гідромотора за експлуатаційними параметрами без розбирання. Результати дослідження можуть бути використані для підвищення надійності гідроприводів та вдосконалення методів діагностики самохідної техніки. /// EN: This paper examines the patterns of change in the output characteristics of a planetary (orbital) hydraulic motor during operation, taking into account its technical condition. The relevance of the study stems from the need to improve the reliability of hydraulic drives in self-propelled vehicles and the lack of effective approaches to diagnosing hydraulic machines without disassembling them. It has been established that the key factor determining the technical condition of a hydraulic motor is the diametrical clearance between the rotors, which changes due to wear and directly impacts functional parameters of a planetary (orbital) hydraulic motor. To study the influence of operational factors, a full factorial experiment was used, varying shaft load, hydraulic fluid flow rate, and diametrical clearance. The response functions selected were shaft speed, pressure drop, and volumetric, mechanical, and overall efficiency. Based on the experimental results, mathematical models were developed in the form of regression equations that adequately describe the relationship between the determining factors and the initial hydraulic motor characteristics with a confidence level of 0.95. It was found that within a diametrical clearance range of 0.02–0.16 mm, efficiency factors remain relatively stable and do not reflect the actual degree of wear, limiting their use as diagnostic parameters. At the same time, the hydraulic motor shaft speed is the most sensitive indicator, decreasing with both increasing load and increasing clearance and decreasing hydraulic fluid flow. Critical operating conditions were identified, in which a significant increase in diametrical clearance (up to 0.23 mm) leads to a sharp drop in speed and loss of hydraulic motor performance. Based on the obtained dependencies, an approach is proposed for determining the technical condition of a planetary hydraulic motor based on measured operating parameters (rotational speed, flow rate, pressure drop) without dismantling the equipment. The practical significance of these results lies in their potential use in developing diagnostic and resource forecasting systems for hydraulic drives, which will lead to increased operational efficiency and reduced maintenance costs for self-propelled equipment.
Prediction of changes in output characteristics of a planetary hydraulic motor under operating conditions
Keywords: крутний момент; витрата робочої рідини; діаметральний зазор; частота обертання; повно- факторний експеримент; torque; working fluid flow rate; diametrical clearance; rotational speed; full-factorial experiment